Penentuan Efisiensi Immobilisasi Kromium (VI) Pada Geopolimer Abu Sekam Padi Dengan Uji TCLP (Toxicity Characteristic Leaching Procedure) - Kun Sri Budiasih (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2011)
This research aimed to determine the efficiency of immobilization of Cr(VI) on the rice husk ash based geopolymer with a TCLP (Toxicity Characteristic Leaching Procedure) study. The TCLP was refer to the standard method from Japan Environmental Agency. There were three variables used i.e., concentration of Cr(VI) impregnated, particles size, and the kind of leaching water. Determination of immobilization efficiency was done by calculate the concentration of Cr(VI) in the leachate water after the leaching processes. Quantitative measurement of the chromium was done by Uv-Vis spectrometer with biphenyl carbazid reagent. Immobilization of Cr(VI) on the rice husk ash based geopolymer was establish until 25 ppm Cr impregnated. The efficiency of the immobilization can reach 90% - almost 100% depend on the variable of leaching processes. Keywords: eficiency, immobilization, geopolimer, rice husk ash, TCLP study